Essays on the influence of NHC (Nutrition and Health Claims) on consumer response - Sutil, Bruno do Nascimento (2023)
This dissertation explores the historical and contemporary influences of the food industry, media, and regulatory interventions on consumer perceptions and choices. It emphasizes the role of Nutrition and Health Claims (NHC) and Front-of-Package Nutritional Labeling (FoPNL) in shaping consumer understanding. The study highlights the challenges posed by misleading information in packaging and advertising, necessitating government regulations to ensure accurate food communication. Central to the analysis is the health halo effect, where a single piece of information, like NHC, influences overall product perceptions. The research acknowledges consumer agency in decision-making and delves into cognitive processes, such as cognitive dissonance, affecting choices. Divided into three articles, the dissertation systematically reviews the impact of NHC on consumer perceptions, explores the relationship between NHC's health halo effect and cognitive dissonance, and tests the limitations of NHC and FoPNL on food products, providing valuable insights into the intricate dynamics of food communication and consumer behavior.